Rheological properties of native and modified corn starches in the presence of hydrocolloids - Shaari, Nur Atiqah; Sulaiman, Rabiha; Cheok, Choon Yoong (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2017)
Starch and hydrocolloids were often used together in food industry to modify the rheological properties with the aim to enhance the starch tolerance to processing conditions. As such, the rheological properties of xanthan gum (XG), carrageenan, high (HMP) and low methoxyl pectin (LMP), with native corn starch (NCS) and modified corn starch (MCS) at different temperature were evaluated in this study. The flow behavior index (n) of corn starch-hydrocolloid mixtures were observed in the range from 0.160 to 0.604 where indicated the shear thinning behavior. The addition of hydrocolloids increased the apparent viscosity of the starch system. NCS mixtures showed consistency index (K) and apparent viscosities (na,100) decreased with increase in the temperature. The addition of XG and carrageenan increased the storage (G’) and loss (G”) moduli. Among the hydrocolloids, the XG addition to the NCS exhibited superior viscoelastic properties as evidenced by the highest G’ and lowest tan δ values. XG was observed capable to increase while pectin reduced the solid-like starch system. This result provides pragmatic data for food engineer in process design and food product development by minimizing the cost of trial and error.